2010
DOI: 10.1038/onc.2010.194
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AP-1 by SARI negatively regulates transformation progression mediated by CCN1

Abstract: Enhanced expression of the CCN family of secretory integrin-binding proteins correlates with many essential components of the cancerous state, including tumor cell adhesion, proliferation, invasion and migration. Consequently, CCN1 expression is elevated in various cancers, including breast cancer, and its expression directly correlates with poor patient prognosis. Using subtraction-hybridization, combined with induction of cancer cell terminal differentiation, we cloned SARI (suppressor of activator protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 44 publications
1
51
0
Order By: Relevance
“…Mechanistically, BATF2 overexpression dramatically impaired activator protein (AP)-1 function via the direct binding with c-Jun (a critical component of AP-1). Our findings are consistent with the results from a recent study, which confirmed the interaction between BATF2 and c-Jun/AP-1 (23). AP-1 is a pivotal regulator of many signaling pathways in a wide spectrum of cell types and is critical for mitogenesis, apoptosis, and tumorigenesis in a cell type-specific manner (24,33,34).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Mechanistically, BATF2 overexpression dramatically impaired activator protein (AP)-1 function via the direct binding with c-Jun (a critical component of AP-1). Our findings are consistent with the results from a recent study, which confirmed the interaction between BATF2 and c-Jun/AP-1 (23). AP-1 is a pivotal regulator of many signaling pathways in a wide spectrum of cell types and is critical for mitogenesis, apoptosis, and tumorigenesis in a cell type-specific manner (24,33,34).…”
Section: Discussionsupporting
confidence: 82%
“…4B). In addition, we also investigated the effects of BATF2/c-Jun/AP-1 on the levels of CCN1 and WAF1, which play key roles in the progression of a diverse range of human malignancies (23,24). Western blots showed that the expression of WAF1 was significantly increased by BATF2 overexpression in colorectal cancer cells, but CCN1 levels did not change (Supplementary Fig.…”
Section: Batf2 Downregulates Met Expression By Inhibiting Transcriptimentioning
confidence: 99%
“…mda-9/syntenin is colocalized with focal adhesion kinase (FAK) and facilitates fibronectin (FN)-induced phosphorylation of FAK, with subsequent activation of p38 and JNK MAPKs as well as nuclear factor-B (9,10). mda-9/syntenin may interact directly with c-Src, and this interaction correlates with increased formation of active FAK-c-Src signaling complexes (12,13), which are important for regulation of migration machinery (14). We recently showed that transient induction of mda-9/syntenin during adhesion to FN is dependent on PKC␣ activation and enhances the FN-induced assembly of integrin ␤1 signaling complexes with FAK and c-Src, activating FAK and its downstream pathways (15).…”
Section: Pdzmentioning
confidence: 99%
“…Enhanced expression of the Calcineurin family of secretory integrin-binding proteins has been correlated with multiple cancer-associated events, including tumor cell adhesion, proliferation, invasion and migration. Consequently, PPP3CA expression has been demonstrated to be elevated in various cancers, including breast cancer, with its expression directly correlated to patient prognosis (Dash et al, 2010). PPP3CA is also thought to play diverse roles in survival and angiogenesis (Dash et al, 2010).…”
mentioning
confidence: 99%
“…Consequently, PPP3CA expression has been demonstrated to be elevated in various cancers, including breast cancer, with its expression directly correlated to patient prognosis (Dash et al, 2010). PPP3CA is also thought to play diverse roles in survival and angiogenesis (Dash et al, 2010). In breast cancers, over expression of PPP3CA in MCF-7 human breast cancer cells has been shown to up-regulate MAPK and NFkB signaling in an integrin αvβ3-dependent manner, promoting cell survival and chemoresistance (Vellon et al, 2005) as well as to promote cell growth, migration and angiogenesis in vivo (Tsai et al, 2002).…”
mentioning
confidence: 99%